Aggregate Planning of Batch Plant Operations - SHARMA, DR.ANKUSH (The journal of contemporary issues in business and government, 2021)
Aggregate planning is an analytical tool offering a strategy to meet demand based on capacity constraints. Production and supply of building materials plays an important role in delivering constructed facilities, particularly for concrete and asphalt batch plants. The supply chain of construction materials (e.g., concrete) presents unique challenges, but is a key factor in the successful delivery of facilities. This paper addresses the production and implementation of an integrated planning approach focused on simulation that enables the modeling and organization of the supply chain of a batch factory. The tool is applied to a true case of asphalt production operations, where fluctuating demand affects the production plant's level of service and makes production planning and inventory processes a challenging task. The model quantifies the impact of the asphalt processing plant's different parameters on its level of operation and tries to determine the right solutions for the processing, procurement and delivery processes of the factory.